The Role of Stakeholders in Public Transportation Services Based on Information Technology. Issue 1 (March 2021) - Ahmad, Jamaluddin; Ramadhan, Muhammad Rohady; Nilwana, Andi; Bibin, Muhammad; Ardian, Ani; Sahar,
Abstract: Public transportation in Sidenreng Rappang Regency faces various problems that affect the achievement of tax collection effectiveness. One phenomenon that is often encountered in matters relating to the public transportation tax system is the emergence of an unofficial terminal, irregular tax collection processes, lack of motivation and guidance to tax management officers so that they are less professional in their field duties and public transportation facilities and infrastructure are not yet optimal. For this reason, planning for priority strategies is needed to increase local revenue (PAD). The purpose of this study is to design a priority strategy for increasing local revenue (PAD) through public transportation taxes in Sidenreng Rappang Regency. The research method used is a mixed-methods method. Data were collected through observation and in-depth interviews with stakeholders. Then the data were analyzed using stakeholder analysis methods and process hierarchy analysis. Stakeholders involved in increasing public transport taxes in Sidenreng Rappang Regency are divided into two groups. The first group is the key players. Key player's group stakeholders must be more actively involved in planning and evaluating policy. The second group is the actors. Stakeholder group can bring risks, so their existence needs to be monitored and managed properly. To optimize the role of stakeholder actors, it is necessary to coordinate with key stakeholder groups in determining policy. The priority scale of the policy in increasing public transport taxes is as follows: 1) optimizing training and education programs in improving the quality of human resources and increasing the dissemination to taxpayers; 2) improve public transportation terminal facilities; 3) evaluating Regional Regulation Number 10 of 2010 concerning tax tariffs; and 4) cooperation between other agencies.